Utilizing Technology: Knowledge Applications for Millennial Entrepreneurs - Ardianus Laurens Paulus (ProBisnis : Jurnal Manajemen, 2022)
This study aims to determine the effect of one of the processes in knowledge management, namely knowledge application on millennial entrepreneurs in utilizing technology in business processes. The research sample is millennial entrepreneurs with 153 respondents through an online survey via a google form. Data analysis using confirmatory factor analysis, descriptive test, and regression test. According to the findings of this study, knowledge application has a substantial impact on the use of millennial entrepreneurial technologies. Smartphones are the most commonly utilized information technology media among millennial entrepreneurs in this study. The millennial entrepreneurship promotion media tools studied use social media and the type of business for millennial entrepreneurs is dominated by the fashion business.